Expert C# 2008 Business Objects - Lhotka, Rockford (Apress, 2012)
I have a passion for frameworks. In more than 20 years as a professional developer, I’ve never worked on a computing platform that did everything I needed it to do to build applications productively. The Microsoft .NET platform is wonderful, but it doesn’t always do quite what I want or need. To address those needs, I’m always looking for tools and frameworks, and sometimes I end up creating them myself. A framework is simply the codification of an architecture or design pattern. Before you can have a good framework, you need to have an architecture. That means you need to have a vision and a set of goals both for the architecture and the kinds of applications it should enable. This book is about application architecture, design, and development in .NET using object-oriented concepts. The focus is on creating business objects and implementing them to work in various distributed environments, including web and client/server configurations. The book makes use of a great many .NET technologies, object-oriented design and programming concepts, and distributed architectures. Much of the book walks through the thought process I used in designing and creating the CSLA .NET framework to support object-oriented application development in .NET. This includes a lot of architectural concepts and ideas. It also involves some in-depth use of advanced .NET techniques to create the framework. The book also shows how to make use of the framework to build a sample application with several different interfaces. If you wish, you could skip the framework design chapters and simply make use of the framework to build object-oriented applications.